Pengaruh Model Discovery Learning terhadap Kemampuan Menentukan Imaji dalam Pantun oleh Siswa Kelas XI SMK YPK Medan Tahun Pembelajaran 2014-2015 - Amnur Rifai Dewirsyah; Lidya Yudita Ambara (Departement of Mathematics Education, 2022)
The implementation of learning in schools still pays little attention to the potential skills of students. This can be seen from the low quality or quality of students, especially in determining images in rhymes. This study aims to determine the effect of discovery learning on the ability to determine images in rhymes by class XI students of SMK YPK Medan in the 2014-2015 academic year. The research data was taken from a portion of the population, totaling 160 people and a sample of 65 people, 35 people for the experimental class and 30 people for the control class, the sampling method. The method used in this research is experimental, the method of taking samples is carried out in two classes, namely the experimental class and the control class, the experimental class uses the discovery learning model and the control class uses conventional learning models. The results of this study determine that the images in rhymes using the discovery learning model are in the very good category.